Prevalencia de intentos de autolisis en los adolescentes atendidos en el hospital básico de Yantzaza, del cantón Yantzaza. año 2014 - TAIZHA PAQUI, FLOR MARÍA (2016)
This research work had like purpose to determine the prevalence of suicide attempts in young adolescents treated at the Base Hospital Yantzaza, the technique was used direct observation with its guide instrument, through by reviewing medical records of 54 teenagers who formed the sample. The methodology was used descriptive, retrospective and the realm literature. The results obtained allowed to determine the prevalence of 10.65%, in function of socio-demographic characteristics the predominant age is 16 to 20 years with a percentage of 55.56%, male with 61.11% are ethnic mixed the 62.96%, come from rural areas 61.11%, secondary school with 61.11%, the half economic level corresponds to 75.93%. Within the psychological risk factor is the depression with 37.04%, among the economic factor is the low salary of parents and social factor the heartbreak with 42.59% in each case. It execute an action plan based on educational activities; teenagers training colleges Yantzaza parish , home visits to teenagers and parents with the topic on prevention of suicide attempts ,to help reduce the suicide attempts and deliver an educational brochure to the vocational guidance department. Concluding that the prevalence of suicide attempts are 10.65%, due to depression, low-paying parents and heartbreak of young adolescents.